2015
DOI: 10.1007/s12205-015-0602-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of flow past two circular cylinders in tandem and side-by-side arrangement at low Reynolds numbers

Abstract: A numerical simulation was used to compare the characteristics of flows past two cylinders in tandem versus side-by-side arrangements. Numerical experiments were performed at various Reynolds numbers and with different distances between the two cylinders. Diverse characteristics of flow, such as drag force, vortex shedding, and pressure distributions were investigated here. In tandem arrangement, at a certain distance, the drag coefficients of both cylinders change abruptly. However, at other distances, the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
10
16
0
Order By: Relevance
“…In which, the drag coefficient decreases as Re increases. Relationship between C D and Re also shows a good agreement with the previous 196 Liu et al (1998) 1.31±0.049 0.192 Nc b = 160 (Vu et al, 2015) 1.38 0.191 Nc b = 240 (Vu et al, 2015) 1.33 0.186 Nc b = 320 (Vu et al, 2015) 1.303 0.182 a : laboratory experimental studies, Nc b : the number of grid cells on the cylinder. …”
Section: Numerical Validationsupporting
confidence: 86%
See 4 more Smart Citations
“…In which, the drag coefficient decreases as Re increases. Relationship between C D and Re also shows a good agreement with the previous 196 Liu et al (1998) 1.31±0.049 0.192 Nc b = 160 (Vu et al, 2015) 1.38 0.191 Nc b = 240 (Vu et al, 2015) 1.33 0.186 Nc b = 320 (Vu et al, 2015) 1.303 0.182 a : laboratory experimental studies, Nc b : the number of grid cells on the cylinder. …”
Section: Numerical Validationsupporting
confidence: 86%
“…Vu et al (2015) concluded that simulation with 240 grid cells around the cylinder provides the most reasonable computational results under Re = 200. In this study, beside the grid test was presented in Vu et al (2015), two grid resolution schemes with the number of grid cells around cylinder of 160 and 320 were tested under Re = 60 and 100. With these two mesh resolutions, the grid cells in the domain were 173760 and 215680, respectively.…”
Section: Numerical Validationmentioning
confidence: 98%
See 3 more Smart Citations